TINJAUAN LITERATUR TENTANG FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI BELAJAR MATEMATIKA SISWA SEKOLAH DASAR DI INDONESIA - M Mauliddin, Rindu Akbar; Siallagan, Yesica Paulina; Siregar, Sari mutiah; Simamora, Yosua Paskah; Kudadiri, Natalia Rama (Universitas Negeri Medan, 2025)
This study aims to review various theories, factors, and learning strategies that affect the motivation of mathematics learning of elementary school students. The type of research used is a literature review by examining 10 accredited national journals (2020–2025) and 5 latest scientific books relevant to the topic of basic education and learning psychology. The analysis was carried out descriptively through three stages: data reduction, classification, and synthesis of findings. The results of the study showed that the motivation to learn mathematics of elementary school students was influenced by a combination of internal factors (interest, self-confidence), external (teacher strategies, interactive media), and social factors (learning environment support). Strategies such as Realistic Mathematics Education (RME), Project-Based Learning (PjBL), formative assessments, and the use of card-based interactive media have proven to be effective in increasing student engagement. In addition, motivational theories from Deci and Ryan (2017) and Uno (2021) affirm the importance of the role of intrinsic motivation in fostering a sustained interest in learning. This study recommends that elementary school teachers develop contextual, fun, and differential mathematics learning in order to increase students' confidence and motivation to learn optimally.